SYMBOLISM OF IMPERIALISM IN ORWELL'S SHOOTING AN ELEPHANT - Gabriel Wowor; Ceisy N Wuntu; Allysius Rettob (English Education Department, 2021)
The purpose of this study aimed to reveal the symbolism of imperialism in Orwell’s shooting an elephant. The research is categorized as qualitative research since the data were in the form of words and the data was collected from the primary source that is the novel itself, and the secondary sources were from the books, references, and other sources such as the internet that could support this research. This proposed study can be viewed from at least two different angles. First, in term of the data, this study is qualitative in nature in that the data will be in the form of words or quotations, and the analysis will be in narrative form. Secondly, in terms of sources data and how the data is interpreted, the study can also be categorized as a content analysis. The result of this research is revealing the symbols or signs that which is an act of imperialism that happened in Burma through of some important things about imperialism itself such as; The conquest of Burma and British power, The economic exploitation, and The Spread of religion or ideology.